DNA Damage in AML-12 Hepatocytes and 3T3-L1 Adipocytes Treated with Clopidogrel - SÜSLEYİCİ, BELGİN (BENTHAM SCIENCE PUBL, 2021)
Background: Clopidogrel has been commonly prescribed as a selective P2Y(12) receptor antagonist to reduce heart attack and stroke risk. Nearly 10% of absorbed clopidogrel is metabolized to active forms by cytochrome P450 (CYP) enzymes in the liver and 90% to inactive clopidogrel carboxylate by esterases. Objective: Since different forms of clopidogrel have cytotoxic potential, our aim was to determine the effect of 7.5, 40, and 75 mu M clopidogrel over DNA damage in adipocytes and hepatocytes. Methods: In the present study, DNA damage was investigated by Comet analysis using 3T3-L1 adipocytes and Alpha Mouse 12 (AML-12) hepatocytes. Results: DNA fragmentation was found to be increased as a response to 7.5 mu M, 40 mu M, and 75 mu M clopidogrel treatment compared to non-treated control groups in AML-12 hepatocytes (p<0.01, p<0.001, p<0.01 respectively) and 3T3-L1 adipocytes (p<0.001, p<0.001 and p<0.001respectively). DNA damage levels as a response to clopidogrel treatment were found to be higher in 3T3-L1 adipocytes than AML-12 hepatocytes. Also, DNA damage levels in adipocytes and hepatocytes were found to increase dose-dependently for 7.5 and 40 mu M clopidogrel, whereas decreased as a response to 75 mu M. Conclusion: According to our results, clopidogrel results in more DNA damage in adipocytes than in hepatocytes. The molecular mechanism of clopidogrel genotoxicity needs to be further investigated especially in adipose tissue.
Keywords: AML-12 hepatocytes; 3T3-L1 adipocytes; clopidogrel; cell culture; DNA damage; DNA fragmentation; FATTY-ACID OXIDATION; IN-VIVO; INSULIN-RESISTANCE; CYTOCHROME-P450 3A; ADIPOSE-TISSUE; COMET ASSAY; ANTIPLATELET; TICLOPIDINE; CELLS; METABOLISM